High-resolution computed tomography thorax evaluation of sputum positive/CBNAAT positive pulmonary tuberculosis in diabetic and non-diabetic patients - Rout, Bijnan Kumar; Swain, Basanta Manjari; Singh, Mamata; Mohanty, Theeta (Eastern Journal of Medical Sciences, 2020)
Background: Diabetes mellitus (DM) and pulmonary tuberculosis (TB) are major health problems in India. Diabetes being an immunosuppressive state is thought to be a risk factor for acquisition of TB. However, very few researches provide evidence demonstrating whether DM affects radiological diagnostic findings of pulmonary TB. Hence, this novel cross-sectional study was undertaken to find the difference between the high-resolution computed tomography (HRCT) findings of TB patients with diabetes to that from non-diabetics. Material and Methods: HRCT thorax scans were performed in patients diagnosed as pulmonary TB on the basis of sputum positivity or CBNAAT positivity. Patients were divided into diabetic and non-diabetic group. Patient details and clinical history were recorded and HRCT thorax findings were then compared in both groups. Results: Compared to non-diabetic patients (26.5%), the diabetic patients (53.1%) showed a higher detection rate of lesions at the lower lung lobe (p < 0.05), non-segmental consolidation was also higher in diabetic group (28%) compared to non-diabetic group (2%) p < 0.01), cavitary lesion was noted in 37.5% of diabetic group compared to 8.1% of non-diabetic group (p < 0.01). Conclusion: CT findings of TB in diabetic patients are different from those in non-diabetic patients, with a higher occurrence of non-segmental distribution, cavitary lesion and lower lobes are more commonly affected in TB patients with diabetes.